FRICTION AND WEAR OF COMPOSITES WITH POLYTETRAFLUORETHILENE - V.A. KOHANOVSKY; J.A. PETROFF (Advanced Engineering Research, 2009)
Structure of the composites and friction and wear features are described for polymeric polytetrafluorethylene coating.